4x+y=33
X+y=12
Get the y alone, so subtract x by each side to get y= -x+12
Then fill in the equation: 4x + (-x+12)=33, remove the parenthesis and solve to get 3x+12=33. Then subtract 12 from both sides to get 3x=21. Now divide 3x from both sides to get x=7 now, use this x answer for the previous equation, x+y=12. Fill in the x so now it’s (7) + y=12
And then subtract 7 from both sides to get y=5. So for the first slide, x=7 and y=5
For the next slide, you already have y= -x+15. Fill this in for the equation 3x+2y=36. 3x+2(-x+15)=36 distribute to get 3x+-2x+30=36. Subtract the x’s to get an equation of x+30=36. Subtract 30 from both sides to get x=6 and use this for the other equation, y= -x+15 to get y= -6 + 15, which equals y=9. x=6 and y=9
I hope this helped!